Challenge and Prospect of Traditional Chinese Medicine in Depression Treatment - Zhang, Yuan-Wei; Cheng, Yung-Chi (Frontiers in Neuroscience, 2019)
Current medications for depression are inadequate and far from ideal. Development of novel antidepressant drugs is a pressing task. The discovery of ketamine and the related agents represents a new era in drug discovery for rapid treatment of depression. Due to potential neurotoxicity, short-lasting efficacy, limitation of single target approach, and a limited role in depression prevention of these agents, additional approaches or drugs that exert synergy and compatibility with the rapid acting agents are required for a better treatment. Traditional Chinese Medicine (TCM) is a systems medicine and its clinical experience and integrated theory for diagnosis and treatment provides an alternative way for novel drug discovery in depression treatment. In TCM, there are numerous claimed effective antidepressant formulas, but comprehensive research and evidence-based clinical study are required for their acceptance. In this essay, we review current attempts in discovery of new agents, TCM drug formulation, and TCM treatment of depression, and discuss the challenge and opportunity of TCM in the new era of antidepressant discovery. TCM could provide an important resource in discovery of novel agents, assistance of the rapid acting antidepressants, development of new agents for female patients, and prevention of depression at its early stages. Hence, study of depression with TCM not only provides an opportunity to scientifically evaluate the benefits and risks of TCM, but also accelerates to develop novel antidepressant agents by combining the principle of modern molecular medicine with the ideas of the empirical systems medicine.